Heredo-Familial and Pediatric GISTs: Spot the Differences - Alessandro Perez; Daniele Fanale (Scientific Journal of Genetics and Gene Therapy - Peertechz Publications, 2016)
Gastrointestinal stromal tumors (GISTs) are rare sporadic tumors that typically occur late in life, although they are the most common mesenchymal neoplasms of the gastrointestinal tract. GISTs are believed to originate from the Interstitial Cells of Cajal (ICC), a group of cells identified in the wall of the organs of the gastrointestinal tract, which act as a pace-maker for peristalsis and gut movements. However, familial and pediatric cases have also been reported. These rare subsets of GISTs have clinicopathological and molecular features different from their sporadic counterparts. Pediatric GISTs account for only 1% of all the identified cases of GISTs. Most of them lack the gain-of-function mutation in c-KIT or PDGFRA commonly found in adult cases, and may harbor mutations in other genes such as SDH. Gene expression profiling studies of pediatric GISTs show distinct molecular signatures, suggesting a unique origin as compared with adult GISTs. The review discusses also familial GISTs with germline c-KIT or PDGFRA gene mutations and variants harbouring no mutations in these genes such as Carney triad, Carney-Stratakis syndrome, and neurofibromatosis type  1. However, the initial phases of familial GISTs appear biologically similar to those of sporadic GISTs, with similar cytogenetic progression mechanisms and genic expression profiles.